Three-dimensional hydrogen distribution and quantitative determination of titanium alloys via neutron tomography. Issue 12 (15th May 2020) - Yang, Lixia; He, Linfeng; Huang, Danqi; Wang, Yaoqi; Song, Quanwei; Zhao, Lei; Shen, Xuejing; Tian, Zhiling; Wang, Haizhou
Abstract : For the first time, neutron tomography was applied for 3D quantitative hydrogen distribution analysis in titanium alloys following thermohydrogen processing. Abstract : Thermohydrogen processing (THP) is an attractive technique that uses hydrogen as a temporary alloying element to modify the microstructure and properties of titanium alloys. However, the hydrogen diffusion behavior during THP is not fully understood owing to limited scope of methods to detect hydrogen distributions. Herein, we introduce neutron tomography as an efficient tool for three-dimensional (3D) hydrogen distribution analysis and quantitative determination in hydrogenated titanium alloys after THP. Thus motivated, a series of calibration samples of Ti-6Al-4V alloys with varying hydrogen contents were prepared and elaborated neutron tomography experiments and image data processing were performed. In this way, the 3D hydrogen distribution of the hydrogenated samples was obtained and the quantitative relationship between the hydrogen contents and the tomographic images was determined. To the best of our knowledge, this enabled for the first time the direct 3D visualization and characterization of the hydrogen distribution and concentration in titanium alloys after THP. It was deduced that hydrogen diffused from the surface to the interior of the hydrogenated sample in all directions during THP. In addition, the feasibility of neutron tomography for 3D quantitative hydrogen distribution was validated using continuous sample segmentation and the traditional heat conductivity method. Consequently, neutron tomography can be efficient for determining the hydrogen distribution and concentration in bulk metals and shed light on the hydrogen diffusion behavior and the mechanism of hydrogen-related materials and processing.